The Significance of Virtual Technologies in the Organization of the Course “Initial Preparation Until Calling” In the Educational Process - Boltayevich, Rakhimov Farukh (European Journal of Life Safety and Stability (2660-9630), 2023)
this article contains opinions on the use of methods such as lecture, question-and-answer, and practical exercises in the teaching of the “Primary Pre-Convocation” training course based on innovative methods.